Anti-seizure therapy with a long-term, implanted intra-cerebroventricular delivery system for drug-resistant epilepsy: A first-in-man study. (May 2020) - Cook, Mark; Murphy, Michael; Bulluss, Kristian; D'Souza, Wendyl; Plummer, Chris; Priest, Emma; Williams, Catherine; Sharan, Ashwini; Fisher, Robert; Pincus, Sharon; Distad, Eric; Anchordoquy, Tom; et al.
Abstract: Background: A clinical feasibility study was undertaken at a single center of long-term intra-cerebroventricular drug delivery of the anti-seizure medication valproic acid, into the cerebrospinal fluid (CSF) in order to treat drug resistant focal seizures, using an implantable infusion system. The primary objective was to establish the dose range of VPA administered in this manner. Secondarily, safety, pharmacokinetics (PK) and a preliminary estimate of effectiveness were evaluated. Methods: In this single arm study, five adult subjects, with 29–234 focal onset seizures per month from a seizure focus involving the mesial temporal lobe were implanted with the system (clinicaltrials.gov identifier NCT02899611). Oral valproic acid (VPA) had previously been ineffective in all subjects. Post-surgery, pharmacokinetic studies of CSF infused VPA were performed. Valproic acid doses were increased stepwise in a standardised protocol. Findings: The procedure and implantation were well-tolerated by all subjects. Four subjects responded with > 50% seizure reduction at the highest tested dose of 160 mg/day. Two subjects experienced extended periods of complete seizure freedom. All five subjects reported significant quality of life improvement. No clinical dose limiting side effects were encountered and there was no evidence of local periventricular toxicity in three subjects who were evaluated with imaging (T2 MRI). Side effects included nausea and appetite loss but were not dose-limiting. Mean CSF valproic acid levels were 45 μg per ml (range 20–120 μg per ml), with corresponding serum levels of 4–14 μg per ml.  Subjects have received therapy for up to 2.5 years in total . The efficacy analysis presented focuses on the period of time with the current pump with a mean 12.5 months, range 11.5–15 months. Pump failure requiring reimplantation was a significant initial issue in all subjects but resolved with use of pumps suitably compatible with long-term exposure to valproic acid. Interpretation: The study demonstrated that chronic intraventricular administration of valproic acid is safe and effective in subjects with medically refractory epilepsy over many months. The procedure for implanting the infusion system is safe and well-tolerated. High CSF levels are achieved with corresponding low serum levels and this therapy is shown to be effective despite unsuccessful earlier use of oral valproate preparations. Drug side effects were minimal. Funding: The study was funded by Cerebral Therapeutics Inc., Suite 137 12635 East Montview Blvd Aurora CO 80045.